2017
DOI: 10.1590/1413-81232017224.12852015
|View full text |Cite
|
Sign up to set email alerts
|

Fatores determinantes de conhecimentos, atitudes e práticas em DST/Aids e hepatites virais, entre jovens de 18 a 29 anos, no Brasil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
34

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 5 publications
1
22
0
34
Order By: Relevance
“…Thus, it can be noted that the elderly participants in the study are prone to risk behaviors, thus highlighting health education as the driving force for establishing a bond, in order to ensure the principle of equity in the construction of knowledge in health for self-care. 8,16 The results show that the elderly disregard the possibility of contagion during the asymptomatic period of the disease, since the person with the AIDS virus will always have the symptoms of the disease. For this group, when thinking about HIV/AIDS, it is related to a severe and incurable disease, not understanding the difference between being a carrier of the HIV virus and manifesting the symptoms of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, it can be noted that the elderly participants in the study are prone to risk behaviors, thus highlighting health education as the driving force for establishing a bond, in order to ensure the principle of equity in the construction of knowledge in health for self-care. 8,16 The results show that the elderly disregard the possibility of contagion during the asymptomatic period of the disease, since the person with the AIDS virus will always have the symptoms of the disease. For this group, when thinking about HIV/AIDS, it is related to a severe and incurable disease, not understanding the difference between being a carrier of the HIV virus and manifesting the symptoms of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…The association between knowledge and family arrangement revealed that living with a partner is a predictor of less knowledge about syphilis. Young people married or living with a partner have greater individual vulnerability than single people due to the lower adoption of preventive measures and the search for information on STI/AIDS 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Black women also seem to be highly vulnerable to STIs, HIV/AIDS, and the explanatory hypotheses for this evidence are socioeconomic inequalities and institutional racism (8) . Vulnerability to STI transmission is also found especially in adolescents and is associated with social determinants, which involve the need for habits of talking about sexuality, integration between parents and health professionals, internet access, and considering alcohol consumption (9) .…”
Section: Introductionmentioning
confidence: 99%